Penanaman Karakter Religius Melalui Program Tahfidz di MTsN 1 Lima Puluh Kota - Ardina Khoirunnisa; Fauzan Fauzan; Ulva Rahmi; Alimir Alimir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to describe and analyse the cultivation of religious character through the tahfidz Al-Qur'an program at MTsN 1 Lima Puluh Kota. A descriptive qualitative approach was used in this study, with data collected through observation, interviews, and documentation. The results showed that the tahfidz programme in superior VIII grade has had a positive impact on the formation of students' religious character. The cultivation of religious character is carried out through various methods, such as exemplary teachers, habituation, advice, and punishment. Exemplary teachers, such as examples of polite behaviour and dressing according to sharia, provide good examples to students. Habituation, such as praying together before learning and praying zuhur in congregation, forms positive habits in worship. Brief advice from teachers helps students understand the importance of discipline and obedience in religion. Meanwhile, punishment, such as repeating one page of memorisation backwards, is used as an effort to correct the behaviour of students who do not comply with the rules. This study also shows that the Qur'an memorisation programme not only improves students' ability to memorise the Qur'an, but also forms a better person in worship and morals. However, there are still some obstacles in the implementation of this programme, such as students' lack of awareness of religious obligations and lack of religious attitudes. Therefore, it is recommended that the tahfidz programme continue to be improved and supported by all relevant parties to achieve the goal of forming better religious characters in students.